1998
DOI: 10.1016/s0006-3495(98)77525-3
|View full text |Cite
|
Sign up to set email alerts
|

New Photocycle Intermediates in the Photoactive Yellow Protein from Ectothiorhodospira halophila: Picosecond Transient Absorption Spectroscopy

Abstract: Previous studies have shown that the room temperature photocycle of the photoactive yellow protein (PYP) from Ectothiorhodospira halophila involves at least two intermediate species: I1, which forms in <10 ns and decays with a 200-micros lifetime to I2, which itself subsequently returns to the ground state with a 140-ms time constant at pH 7 (Genick et al. 1997. Biochemistry. 36:8-14). Picosecond transient absorption spectroscopy has been used here to reveal a photophysical relaxation process (stimulated emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
280
2

Year Published

2001
2001
2010
2010

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(308 citation statements)
references
References 28 publications
26
280
2
Order By: Relevance
“…In the dark or ground state, the deprotonated 4-hydroxycinnamic acid chromophore is completely shielded from solvent in the chromophore binding pocket and is stabilized in the trans configuration by participation of its phenolate oxygen in a distal hydrogen bonding network consisting of Tyr-42, Glu-46 and Thr-50. After excitation by blue light, the ground state, whose maximal absorption is at 446 nm, converts through a series of red-shifted intermediates I 0 , I 0 ‡ , and I 1 , in picoseconds, hundreds of picoseconds, and nanoseconds respectively (14), before decaying to a blue-shifted intermediate I 2 , which completes the photocycle by reverting to the ground state in hundreds of milliseconds (15). Because it is the longest-lived state in the photocycle, I 2 is considered to be the ''signaling state'' of E-PYP and is associated with structural heterogeneity (12), partial protein unfolding (16), and transient exposure of hydrophobic residues (17,18).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the dark or ground state, the deprotonated 4-hydroxycinnamic acid chromophore is completely shielded from solvent in the chromophore binding pocket and is stabilized in the trans configuration by participation of its phenolate oxygen in a distal hydrogen bonding network consisting of Tyr-42, Glu-46 and Thr-50. After excitation by blue light, the ground state, whose maximal absorption is at 446 nm, converts through a series of red-shifted intermediates I 0 , I 0 ‡ , and I 1 , in picoseconds, hundreds of picoseconds, and nanoseconds respectively (14), before decaying to a blue-shifted intermediate I 2 , which completes the photocycle by reverting to the ground state in hundreds of milliseconds (15). Because it is the longest-lived state in the photocycle, I 2 is considered to be the ''signaling state'' of E-PYP and is associated with structural heterogeneity (12), partial protein unfolding (16), and transient exposure of hydrophobic residues (17,18).…”
mentioning
confidence: 99%
“…Because it is the longest-lived state in the photocycle, I 2 is considered to be the ''signaling state'' of E-PYP and is associated with structural heterogeneity (12), partial protein unfolding (16), and transient exposure of hydrophobic residues (17,18). The photocycle and its intermediates have been studied by a number of crystallographic (9-11, 19, 20) and spectroscopic methods (12,14,15,(21)(22)(23)(24). Although these studies have contributed a great deal to understanding the photocycle dynamics of E-PYP, a unified picture of the photocycle and its intermediates has yet to emerge; sometimes contradictory results have been obtained by using these different methodologies, and it has not been possible to correlate any of its spectroscopic states with a biologically relevant signaling state.…”
mentioning
confidence: 99%
“…More recent studies using picosecond (28) and femtosecond (29) spectroscopic techniques at room temperature also have revealed the presence of two early photochemical intermediates (I o and I o ‡ ) exhibiting absorption maxima around 510 nm, close to the spectroscopic feature of PYP B at low temperature (27). In addition, Devanathan et al (29) have detected an alternative route for PYP excitation and photochemistry initiated by excitation at 395 nm, on the blue edge of the observed absorption band.…”
Section: The Photocycle Of the Pyp: A Brief Outlookmentioning
confidence: 93%
“…The isolated protein displays photochemical activity based on the photoisomerization (32) of its p-coumaric acid (pCA) chromophore (33,34). Time-resolved visible (35,36) and FTIR (37) spectroscopic studies have revealed a series of intermediates in the PYP photocycle (38). The two states of PYP that are relevant to the work presented here are the initial dark state of PYP (pG) and the longest-lived intermediate (pB), which forms in 1 ms and thermally decays to the pG state on a second time scale.…”
Section: Background On the Photoactive Yellow Protein Systemmentioning
confidence: 99%